The Art of Sound: Phono-Stylistic Perspectives in Bohemian Rhapsody - Azzahra, Sekar; Ilma, Dzikri; Simanjuntak, Ivan Fernando; Rangkuti, Rahmadsyah (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study examines the phonetic and stylistic elements of "Bohemian Rhapsody" by Queen, a song renowned for its distinctive structure and complex themes. It redirects attention from the previously explored cultural, narrative, and biographical elements to investigate the overlooked phonological characteristics that contribute to its aesthetic and emotional resonance. Employing a qualitative methodology, the song’s lyrics were transcribed phonetically using the International Phonetic Alphabet (IPA) to identify dominant consonants and vowels. The results indicate that consonants such as /d/, /s/, /l/, and /n/, along with vowels such as /ɪ/, /ə/, and /aɪ/, play a crucial role in defining the sound quality of the lyrics. These phonological features enhance the song's musicality while emphasizing its narrative tension and emotional depth. The interplay of these sounds creates a dynamic auditory experience that aligns with the song’s shifting emotional landscapes. The study concludes that the phonological elements in Bohemian Rhapsody function as integral carriers of meaning, enriching its thematic and emotional layers. This research bridges linguistic analysis with musical narrative, demonstrating how phono-stylistics can uncover the deeper aspects of iconic musical texts and fostering interdisciplinary dialogue in linguistics, musicology, and cultural studies. The findings imply that similar approaches can be applied to other complex musical compositions, opening new avenues for analyzing the interplay between language and music in various cultural contexts